Spatial modeling reveals nuclear phosphorylation and subcellular shuttling of YAP upon drug-induced liver injury - Wehling, Lilija; Keegan, Liam; Fernández-Palanca, Paula; Hassan, Reham; Ghallab, Ahmed; Schmitt, Jennifer; Tang, Yingyue; Le Marois, Maxime; Rössler, Stephanie; Schirmacher, Peter; Kummer, Ursula; Hengstler, Jan G; et al. (eLife, 2022)
The Hippo signaling pathway controls cell proliferation and tissue regeneration via its transcriptional effectors yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ). The canonical pathway topology is characterized by sequential phosphorylation of kinases in the cytoplasm that defines the subcellular localization of YAP and TAZ. However, the molecular mechanisms controlling the nuclear/cytoplasmic shuttling dynamics of both factors under physiological and tissue-damaging conditions are poorly understood. By implementing experimental in vitro data, partial differential equation modeling, as well as automated image analysis, we demonstrate that nuclear phosphorylation contributes to differences between YAP and TAZ localization in the nucleus and cytoplasm.